Teaching science language grammar to would be translators in vocationally oriented language learning via m-learning - Chernova, Oxana; Litvinov, Aleksandr; Telezhko, Irina; Ermolova, Tatiana (Frontiers in Education, 2022)
Today, as pandemic has shown, m-learning has turned into the only possible form of education in numerous cases. To take full advantage of m-learning, one should create a suitable environment and choose appropriate techniques to provide the desired results. This study aims to prove the efficiency and effectiveness of teaching science language grammar to would-be translators in vocationally oriented language learning (VOLL) via m-learning within a student-centered approach. The research covered the spring semesters of 2019–2020, 2020–2021, sampling 120 second-year students from Peoples’ Friendship University of Russia (RUDN University), Academy of Engineering (seven departments). The researchers used theoretical, empirical, and experimental methods and prepared questionnaires and tests as data collection tools. The outcomes revealed all tricky issues for the students among the selected science language grammar points. The students of the experimental group used both MOODLE and the technology developed by the researchers. The experimental groups scored better than the control groups (90.1% vs. 65.4% and 89.5% vs. 67.2% correct answers in the final test, which meets the research criteria) and proved the efficiency and effectiveness of the proposed teaching technology.